Analgesic and Anti-Inflammatory Activities of 80% Methanol Extract and Solvent Fractions of Ehretia cymosa Thonn (Boraginaceae) Leaves in Rodents - Ashagrie G; Abebe A; Umer S (Dove Medical Press, 2023)
Getachew Ashagrie,1 Abiy Abebe,2 Shemsu Umer3 1Department of Pharmacy, College of Health Sciences, Woldia University, Woldia, Ethiopia; 2Biomedical Research Team, Traditional and Modern Medicine Research Directorate, Ethiopian Public Health Institute, Addis Ababa, Ethiopia; 3Department of Pharmacology and Clinical Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Getachew Ashagrie, Tel +251927368467, Email Getachewashagrie16@gmail.comBackground: Ethnobotanical studies in various districts of Ethiopia reported that Ehretia cymosa (E. cymosa) is used for the management of headache, abdominal pain, arthritis and rheumatism. However, there is no scientific investigation done so far to confirm these traditional claims. Thus, the aim of this study was to assess the analgesic and anti-inflammatory effects of the 80% methanol extract and fractions of E. cymosa leaves.Methods: The dried and pulverized leaves of E. cymosa were soaked with 80% methanol to obtain a crude extract. Fractionation was done using chloroform, ethyl acetate and water by a soxhlet apparatus. The analgesic effects of the crude extract and solvent fractions were assessed using acetic acid-induced writhing and hot plate tests whereas anti-inflammatory activities were investigated using carrageenan-induced paw edema and cotton-pellet-induced granuloma models.Results: In all the tested doses, the 80% methanol extract and solvent fractions revealed substantial (p < 0.001) analgesic activities in acetic acid induced writhing test. In the hot plate method, all the tested doses of E. cymosa crude extract and the solvent fractions produced significant analgesic activities (p < 0.05). In the carrageenan-induced acute inflammation model, all tested doses of the crude extract and solvent fractions resulted in a significant decline in paw edema. The 80% methanol extract and solvent fractions of E. cymosa at all the tested doses significantly reduced inflammatory exudates and granuloma mass formations (p < 0.001).Conclusion: From the results of this investigation, it can be stated that 80% methanol extract, aqueous, ethyl acetate and chloroform fractions of E. cymosa exhibited considerable analgesic and anti-inflammatory activities, supporting the plant's traditional use as a remedy for a variety of painful and inflammatory conditions.Keywords: analgesic, hot plate, anti-inflammatory, Ehretia cymosa, carrageenan-induced paw edema, cotton pellet granuloma